2016
DOI: 10.3390/microorganisms4030036
|View full text |Cite
|
Sign up to set email alerts
|

Streptokinase Treatment Reverses Biofilm-Associated Antibiotic Resistance in Staphylococcus aureus

Abstract: Biofilms formed by Staphylococcus aureus is a serious complication to the use of medical implants. A central part of the pathogenesis relies on S. aureus’ ability to adhere to host extracellular matrix proteins, which adsorb to medical implants and stimulate biofilm formation. Being coagulase positive, S. aureus furthermore induces formation of fibrin fibers from fibrinogen in the blood. Consequently, we hypothesized that fibrin is a key component of the extracellular matrix of S. aureus biofilms under in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
0
18
1
1
Order By: Relevance
“…Fibrinolysins can degrade cross-linked fibrin and decrease viscosity of purulent fluids, which uPA has been reported to efficiently do (15). Biofilms produced by infectious organisms incorporate fibrin as well as DNA, and expedited degradation by fibrinolysins supplementing antibiotics has also been reported (16). It is also plausible that activity of intrapleural tPA is affected when combined with DNase, because the size and quality of DNA fragments can alter tPA activity or that of uPA (17).…”
Section: Perspectivementioning
confidence: 99%
“…Fibrinolysins can degrade cross-linked fibrin and decrease viscosity of purulent fluids, which uPA has been reported to efficiently do (15). Biofilms produced by infectious organisms incorporate fibrin as well as DNA, and expedited degradation by fibrinolysins supplementing antibiotics has also been reported (16). It is also plausible that activity of intrapleural tPA is affected when combined with DNase, because the size and quality of DNA fragments can alter tPA activity or that of uPA (17).…”
Section: Perspectivementioning
confidence: 99%
“…In an experimental animal study, Kwiecinski et al [19] found that precoating of the surface of indwelling medical devices with plasminogen activators resulted in less fibrin deposition on the implant surface which reduced the attachment of free-floating bacteria with subsequent biofilm formation. Similarly, Jørgensen et al [20] and Hogan et al [21] detected that biofilm dispersal fibrinolytic agents increase the penetration and effect of antibiotics in biofilm-related infections. Since TA has an anti-fibrinolytic effect, in the context of previously mentioned studies, TA administration should be associated with a higher risk of biofilm formation and subsequent acute and delayed PJI.…”
Section: Discussionmentioning
confidence: 93%
“…Converting biofilm bacteria to their planktonic form may increase bacterial cell susceptibility to commonly used systemic antibiotics. Some examples that target the matrix components of biofilm include enzymatic treatments such as trypsin, dispersin B, lysostaphin, and DNases 142–144 . Additionally, fibrinolytics like streptokinase or nattokinase break down the fibrin matrix within biofilm and decrease the MBEC of available systemic antibiotics 143,144 .…”
Section: New Advancements In the Treatment Of Musculoskeletal Infectionmentioning
confidence: 99%
“…Another strategy for triggering biofilm dispersal includes targeting the quorum sensing system. For example, treatment in vitro with autoinducing peptide type I, a critical component of the quorum sensing system, was able to trigger dispersal of MRSA on titanium discs 144 . RNAIII‐inhibiting peptide (RIP) is another peptide that targets the quorum sensing system in S. aureus by competing with RNAIII‐activating peptide which results in decreased cell adhesion and agr activation and has been investigated to reduce S. aureus adhesion to foreign materials 145 .…”
Section: New Advancements In the Treatment Of Musculoskeletal Infectionmentioning
confidence: 99%
See 1 more Smart Citation